Who is discriminated most in the EU? An analysis of the Covid-19 compensation fund - Alfred Greiner; Benjamin Owusu (Bielefeld University, Faculty of Business Administration and Economics, 2021)
The European Union has set up a fund in order to compensate countries for damages resulting from Covid-19 that hit the economies in an asymmetric way. We argue that payments should be based only on relative damages, expressed as losses relative to GDP, and any distribution mechanism implying that damages in the countries are treated differently is discriminatory. Hence, we compute the compensation payments if the resources of the fund are spent according to the relative loss in GDP. Finally, we compare the compensations relative to the losses in GDP, resulting from the application of that principle, with those obtained by distributing the funds as suggested by the Council of the European Union. Our results provide evidence of discrimination by the EU Covid-19 compensation package.
urn:nbn:de:0070-pub-29521781
Keywords: H12; H84; 330; Covid-19; European Union; transfers; discrimination